Pengaruh Label Halal dan Harga dalam Keputusan Pembelian Produk Makanan dan Minuman - Mifta Hasda; Mohd Winario; Saru Reza (Multidisciplinary Journal of Religion and Social Sciences, 2026)
This study aims to analyze the effect of halal labeling and price on purchasing decisions for food and beverage products among students of the Faculty of Islamic Studies at Universitas Pahlawan Tuanku Tambusai. The study employs a quantitative approach using a survey method to obtain objective empirical data. The research sample consists of 28 respondents selected through purposive sampling, with the criteria of active students who have previously purchased packaged food and beverage products. Data were collected through the distribution of questionnaires using a five-point Likert scale to measure respondents’ perceptions of the research variables. The collected data were then analyzed using multiple linear regression analysis with the assistance of SPSS version 22. The results indicate that halal labeling has a positive and significant effect on purchasing decisions, while price does not have a significant partial effect. However, simultaneously, halal labeling and price have a significant effect on purchasing decisions for food and beverage products. These findings confirm that the halal aspect is the main consideration for students in determining purchasing decisions compared to the price factor.